(untitled) (Scientific journal of the Fergana State University, 2024)
The topic of forming students competence based on the requirements of international assessment programs is an urgent educational and scientific topic. In this article, advanced foreign international assessment programs such as PISA, PIRLS, TIMSS, etc., are studied in order to improve and modernize the quality of national education. Based on them, opinions about the role and importance of the formation of students’ competence in the educational system are highlighted.